Use of 3T MRI and an unspoiled 3D fast gradient echo sequence for porcine knee cartilage volumetry: Preliminary findings. Issue 1 (2nd November 2012) - Cromer, Megan S.; Foster, Sheryl L.; Bourne, Roger M.; Fransen, Marlene; Fulton, Roger; Wang, Shih‐Chang
<x xml:space="preserve">Abstract</x> Purpose To assess the utility of knee cartilage volumetry using an unspoiled fat‐suppressed 3D fast gradient echo (FGRE) sequence at 3T. Materials and Methods Sagittal magnetic resonance (MR) images were obtained with an unspoiled fat‐suppressed 3D FGRE sequence in eight porcine knees. Manual segmentation was used to derive the cartilage volume. This volume was compared to a volume measurement of cartilage scraping specimens obtained by water displacement. Imaging was repeated five times in four of the knees to assess interscan volume measurement reproducibility and calculate precision error. A single 3D dataset was manually segmented five times at weekly intervals to assess intraobserver volume measurement reproducibility. Results Total cartilage volume obtained from MRI and water displacement correlated well (r = 0.75). The interscan reproducibility of total volume measurements, expressed as the coefficient of variation (CV), was 4.2%, and the precision error (root mean square [RMS] CV) was 4.1%. The CV of intraobserver estimates of total cartilage volume by MRI was 3.6%. Conclusion Interscan reproducibility of quantification of total cartilage volume and reproducibility of the manual segmentation technique were both high (>95%). Accurate and reproducible cartilage volumetry can be obtained by using a clinical unspoiled fat‐suppressed 3D FGRE acquired at 3T MRI. J. Magn. Reson. Imaging 2013;38:245–250. © 2012 Wiley Periodicals, Inc.